A Modular, DNA‐Based Beacon for Single‐Step Fluorescence Detection of Antibodies and Other Proteins. (4th September 2015) - Ranallo, Simona; Rossetti, Marianna; Plaxco, Kevin W.; Vallée‐Bélisle, Alexis; Ricci, Francesco
Abstract: A versatile platform for the one‐step fluorescence detection of both monovalent and multivalent proteins has been developed. This system is based on a conformation‐switching stem–loop DNA scaffold that presents a small‐molecule, polypeptide, or nucleic‐acid recognition element on each of its two stem strands. The steric strain associated with the binding of one (multivalent) or two (monovalent) target molecules to these elements opens the stem, enhancing the emission of an attached fluorophore/quencher pair. The sensors respond rapidly (<10 min) and selectively, enabling the facile detection of specific proteins even in complex samples, such as blood serum. The versatility of the platform was demonstrated by detecting five bivalent proteins (four antibodies and the chemokine platelet‐derived growth factor) and two monovalent proteins (a Fab fragment and the transcription factor TBP) with low nanomolar detection limits and no detectable cross‐reactivity.